CLINICAL AND CHEST X-RAY FEATURES OF PNEUMONIA IN INJECTING-DRUG USERS - Butova, T. S.; Butov, D. O.; Martynchyk, O. S.; Sinichenko, O. S.; Martymianova, L. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
On an example of a clinical case in a patient with drug addiction, the reviewed clinical and chest X-ray features of community-acquired pneumonia, the diagnostic algorithms and the differential diagnostics are based on the recommendations of the Ukrainian Association of Pulmonology. The treatment strategy of the patient in the conditions of an ambulatory are described. Community-Acquired pneumonia acquired by intravenous drug use is characterized by a severe course, febrile body temperature, severe specific lung disease. On the example of this clinical case, the importance of express diagnostics of pneumonia at the ambulatory stage wasconfirmed to determine the correct tactics of patient management.